2021
DOI: 10.1136/bmjgh-2020-003750
|View full text |Cite
|
Sign up to set email alerts
|

Delivering maternal and neonatal health interventions in conflict settings: a systematic review

Abstract: BackgroundWhile much progress was made throughout the Millennium Development Goals era in reducing maternal and neonatal mortality, both remain unacceptably high, especially in areas affected by humanitarian crises. While valuable guidance on interventions to improve maternal and neonatal health in both non-crisis and crisis settings exists, guidance on how best to deliver these interventions in crisis settings, and especially in conflict settings, is still limited. This systematic review aimed to synthesise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 110 publications
0
33
0
1
Order By: Relevance
“…To some extent, this reflects broader trends in research on SRH in humanitarian settings. Recent reviews of SRH service delivery in humanitarian settings note a lack of research on effective delivery strategies for SRH interventions in conflict-affected settings, especially in areas where health infrastructure has been damaged or services limited [ 49 , 50 ]. Authors examining evidence of effectiveness and utilization of SRH services also found few studies describing how interventions are coordinated or evaluating interventions as part of a coordinated package of SRH services [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, this reflects broader trends in research on SRH in humanitarian settings. Recent reviews of SRH service delivery in humanitarian settings note a lack of research on effective delivery strategies for SRH interventions in conflict-affected settings, especially in areas where health infrastructure has been damaged or services limited [ 49 , 50 ]. Authors examining evidence of effectiveness and utilization of SRH services also found few studies describing how interventions are coordinated or evaluating interventions as part of a coordinated package of SRH services [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of discussion on commodity security and financing considerations was surprising. Other reviews and case studies have highlighted safety and security constraints, movement restrictions, forced displacement, supply chain disruptions, and shortages of skilled health professionals as barriers to SRH intervention delivery in conflict-affected settings [ 49 , 50 , 58 ]. None of the studies we reviewed mentioned barriers to self-care or implementation considerations that are specific to humanitarian contexts or ways in which strategies for introduction, promotion, monitoring, support or sustainability of self-care were tailored to account for health system disruptions or humanitarian access constraints.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review on nutritional interventions is a part of series of reviews in conflict settings which includes delivery of mental health, sexual and reproductive health and other interventions in conflict settings. [11][12][13][14][15][16][17][18] This review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (online supplemental appendix 1), 19 and its protocol is registered with PROSPERO (the international prospective register of systematic reviews, www. crd.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding socio-cultural and contextual factors underpinning acceptance of mistreatment in childbirth, related to conflict, insecurity, gender and power dynamics, is critical for improving the quality of maternity care in afghanistan and similar fragile and conflict affected settings.The number of women and children affected by armed conflict has grown steadily since 2000; during this period, at least 630 million women and children-10% of women and 16% of children worldwide-have either been displaced by conflict or living dangerously close to armed conflict events (Bendavid et al, 2021). With this shifting global landscape, there is growing attention to quality of health services in crisis-affected settings, with efforts to review evidence on health system quality (Jordan et al, 2021), understand context-specific challenges to delivery of quality care (Munyuzangabo et al, 2021), and develop operational guidance for improving quality of care (Syed et al, 2020) in areas affected by conflict and fragility.As authors of the Lancet Maternal Series in 2016 emphasize: Every woman, every newborn, everywhere has the right to appropriate, timely, evidence-based, respectful care (The Lancet, 2016). Mistreatment during childbirth has been highlighted as a significant obstacle in reducing maternal and newborn mortality around the globe -it contributes to negative user experiences and can be a significant deterrent to the uptake of facility-based childbirth (…”
mentioning
confidence: 99%
“…The number of women and children affected by armed conflict has grown steadily since 2000; during this period, at least 630 million women and children-10% of women and 16% of children worldwide-have either been displaced by conflict or living dangerously close to armed conflict events (Bendavid et al, 2021). With this shifting global landscape, there is growing attention to quality of health services in crisis-affected settings, with efforts to review evidence on health system quality (Jordan et al, 2021), understand context-specific challenges to delivery of quality care (Munyuzangabo et al, 2021), and develop operational guidance for improving quality of care (Syed et al, 2020) in areas affected by conflict and fragility.…”
mentioning
confidence: 99%